ATP modulation of osmotically activated anionic current in the membrane of Phycomyces blakesleeanus sporangiophore - Katarina S. Stevanović; Bogdana Čepkenović; Strahinja Križak; Tanja Pajić; Nataša V. Todorović; Miroslav Ž. Živić (Scientific Reports, 2023)
Abstract Ion channels are vital components of filamentous fungi signaling in communication with their environment. We exploited the ability of the apical region of growing sporangiophores of Phycomyces blakesleeanus to form membrane-enveloped cytoplasmic droplets (CDs), to examine ion currents in the filamentous fungi native plasma membrane. In hypoosmotic conditions, the dominant current in the CDs is ORIC, an osmotically activated, anionic, outwardly rectified, fast inactivating instantaneous current that we have previously characterized. Here, we examined the effect of ATP on ORIC. We show that CDs contain active mitochondria, and that respiration inhibition by azide accelerates ORIC inactivation. ATP, added intracellularly, reduced ORIC run-down and shifted the voltage dependence of inactivation toward depolarized potentials, in a manner that did not require hydrolysis. Notably, ATP led to slowing down of ORIC inactivation, as evidenced by an increased time constant of inactivation, τin, and slower decline of τin during prolonged recordings. Flavonoids (genistein and quercetin) had the effect on ORIC opposite to ATP, acting as current inhibitors, possibly by disrupting the stabilizing effect of ATP on ORIC. The integration of osmotic sensing with ATP dependence of the anionic current, typical of vertebrate cells, is described here for the first time in filamentous fungi.